REVITALIZATION OF ISLAMIC EDUCATION IN THE PERSPECTIVE OF RAHMATAN LIL 'ALAMIN TO FORM A GENERATION WITH CHARACTER - Julia Adelina; Iwan Ridwan; Al-Amin (Adisam Publisher, 2026)
This study aims to analyze the revitalization of Islamic education from the perspective of Rahmatan lil ‘Alamin in shaping a globally characterized generation in the era of globalization. The rapid development of technology, digitalization, and socio-cultural transformation has created various challenges for the younger generation, including moral degradation, intolerance, individualism, and the weakening of spiritual values. In this context, Islamic education is required not only to serve as a medium for transmitting religious knowledge but also to be a transformative system capable of fostering spiritual, intellectual, social, and humanitarian values in a balanced manner. This research employs a qualitative approach using the library research method by analyzing various scientific sources such as Scopus-indexed international journals, books, and relevant academic literature related to Islamic education, character education, globalization, and the concept of Rahmatan lil ‘Alamin. The data were analyzed descriptively and critically through stages of literature identification, categorization, interpretation, and theoretical synthesis. The findings indicate that the values of Rahmatan lil ‘Alamin, including tolerance, compassion, justice, moderation, and respect for diversity, are highly relevant in strengthening Islamic education in the modern era. The revitalization of Islamic education can be achieved through curriculum transformation, the integration of digital technology, the strengthening of character education, and the improvement of teachers’ competencies as agents of social transformation. Furthermore, Islamic education based on Rahmatan lil ‘Alamin contributes significantly to the formation of a globally competitive generation that maintains strong moral and spiritual identities while adapting to multicultural global society. This study contributes theoretically by offering a holistic and humanistic paradigm of Islamic education relevant to the challenges of the 21st century.